The Phenomenon of Child Labor and Its Effects in Iraq: The Educational Aspect as a Model - Ahmad, Prof. Dr. Baidaa Mahmoud Ahmed; Awad, Prof. Dr. Amer Hashem Awad (Sulaimani Journal for Humanities, 2026)
The research deals with one of the social phenomena that Iraq suffers from, which is child labor, with its negative effects on the development process in general and on the educational status of this segment in particular. The importance of the research comes from the fact that Iraq, according to population census statistics for the year 2024, is considered one of the young countries, meaning that the number of the group able to work, as well as the number of children, is very large, which means that the future requires finding solutions to overcome this phenomenon. The research will go towards studying the interpretation of the national legal system for child labor, and what this term applies to. The research will also address the causes and effects of this phenomenon and propose a number of solutions to deal with it.
Keywords: Child labour; the effects of the phenomenon of child labour; the issue of education